Strategy for Strengthening the Professionalism of Teaching and Education Personnel at SMPN 15 Mataram - Baiq Nurhani; Lalu Muhammad Izul Islami; Mohammad Mustari (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
This study highlights how SMPN 15 Mataram manages its public relations function and the management of its teaching and administrative staff, from the planning stage to performance evaluation. During the planning stage, the school identifies the number of study groups (rombel) as the basis for determining teacher needs. Teacher placement is designed by the vice principal for curriculum based on diplomas and formal competencies, while the vice principal for public relations oversees programs within his unit, including the development of the literacy program into the MBG program. The placement of teaching and administrative staff is also aligned with official documents such as certificates of expertise and employment status, including approximately 15 first aid personnel. In terms of performance assessment, the principal acts as the primary assessor through a digital system in the GTK room connected to the KPSN division. Professional development of teachers and staff is carried out through learning communities, scientific papers, and various activities or competitions facilitated by public relations. Performance evaluation is conducted transparently and can be followed up through direct communication with the principal. Overall, public relations and human resource management at SMPN 15 Mataram is systematic, collaborative, and structured.